Advances in Arts-Integrated Pedagogy for Speech Development in Inclusive Secondary Classrooms - Ginikachi Prisca Ifenatuora; Olanrewaju Awoyemi; Fadeke Adeola Atobatele (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This paper explores the integration of arts-based pedagogy into secondary classrooms as a method to support speech development in students with language delays, particularly within inclusive educational settings. Drawing on foundational theories such as Gardner’s Multiple Intelligences, Vygotsky’s Sociocultural Theory, and Dewey’s Art as Experience, the study demonstrates how arts practices—including drama, music, and visual arts—can stimulate verbal expression, boost communicative confidence, and foster social interaction. A review of current practices highlights successful arts-focused programs, such as drama-based interventions and visual arts projects, which have led to improved speech outcomes for adolescents. Despite promising findings, gaps in research are identified, particularly in large-scale longitudinal studies and the development of standardized instructional frameworks. The proposed pedagogical model emphasizes key components like collaboration, creativity, and feedback loops, while providing strategies for inclusive application through differentiated and multimodal learning. Assessment methods, including formative, self, and summative evaluations, are proposed to measure student progress effectively. Implications for educators, curriculum designers, and policymakers stress the importance of integrating arts-based strategies into inclusive education policies. Future research directions focus on longitudinal studies, curriculum development, and the intersection of arts integration with other therapeutic practices to create comprehensive speech development models.
Keywords: Arts-Integrated Pedagogy; Speech Development; Inclusive Education; Secondary Classrooms; Language Delays; Pedagogical Framework